Full Mouth Rehabilitation of a Patient with Uneven Occlusal Plane and Severe Attrition: A Clinical Report (Indian Journal of Forensic Medicine & Toxicology, 2020)
In clinical practice we usually come across cases with severe tooth wear which requires a full mouthrehabilitation. And management of patients with worn-out dentition was always a tough and complexprocedure. For a predictable and favourable treatment outcome a systemic multidisciplinary approach wasrequired. This case report describes the interdisciplinary approach in the treatment of a patient with severeattrition and loss of vertical dimension. After performing endodontic treatment for required teeth, a biteraising transitional prosthesis was given for increasing the VD to acquire essential interocclusal space forpost and core buildups and full coverage restorations. After that the porcelain fused to metal permanentrestoration was fabricated and scrutinized for stable contact in centric and eccentric relation.
Keywords: Attrited teeth, full-mouth rehabilitation, Occlusal splint, vertical dimension of occlusion.